Ledelse av mennesker i det nye arbeidslivet - Bastesen, Jarle; Kåfjord Lange, Birthe; Næss, Hans Erik; Thon, Andreas (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"This book is the first in a series of publications from the Department of Leadership and Organization at Høyskolen Kristiania. Through 12 chapters, we highlight leadership-related issues concerning, among other things, digitalization, employee empowerment, consulting, behavioral biology, mentoring programs, self-leadership, corporate health, trust, and workplace inclusion. The chapters include studies within the business arena, the public sector, sports and the media, touching on one or more key dimensions of the research field: • Good leadership takes into account that people are more than processes. • Good leadership rides on the realization that our scope of action is crucial to how we manage our work. • Good leadership reflects understanding the importance of the context in which people and organizations find themselves • Good leadership means being aware of the relationship between change and continuity On the one hand, the chapters explore themes, cases and concepts that bring the field of research forward, especially in the Norwegian context, with a diversity of theoretical, conceptual and empirical studies. On the other hand, these same chapters challenge a number of assumptions, language choices and claims within management research that can obscure the value of the subject matter for working life in general. As this is a scientific anthology, the chapters are rich in research-based insights into circumstances and processes about which tomorrow's leaders will benefit from knowing. The book is therefore primarily aimed at researchers, managers and leadership developers, but it will also engage students and practitioners with an interest in leadership and management disciplines."